EFFECT OF ATORVASTATIN ON THE FUNCTIONAL STATE OF THE KIDNEYS IN PATIENTS WITH ACUTE CORONARY SYNDROME WHO UNDERWENT PERCUTANEOUS CORONARY ANGIOPLASTY - S. K. Abdusattarova; A. L. Alavy; S. R. Kenjaev (Евразийский Кардиологический Журнал)
According to current investigations statins may prevent contrast induced nephropathy in patients.